2003
DOI: 10.1063/1.1620686
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-dot optical temperature probes

Abstract: The steady-state photoluminescence (PL) properties of cadmium selenide quantum dots (QDs) with a zinc sulfide overlayer [(CdSe)ZnS] can be strongly dependent on temperature in the range from 100 to 315 K. The PL intensity from 50 to 55 Å (CdSe)ZnS QDs in poly(lauryl methacrylate) matrices increases by a factor of ∼5 when the temperature is decreased from 315 to 100 K, and the peak of the emission band is blueshifted by 20 nm over the same range. The change in PL intensity is appreciable, linear, and reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
285
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(304 citation statements)
references
References 16 publications
14
285
2
3
Order By: Relevance
“…For this "critical" size, the QY scales up to 0.47, in reasonable agreement with previous works that report on QY values ranging from 0.25 up to 0.6 for CdTe QDs. 11,23,35 At this point, it should be noted that a small variation in synthesis conditions may result in a large difference in quantum efficiency, even with the same experimental conditions, but different batches. Nevertheless, we ruled out this possibility by repeating the measurements, using completely different batches provided by the same company.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this "critical" size, the QY scales up to 0.47, in reasonable agreement with previous works that report on QY values ranging from 0.25 up to 0.6 for CdTe QDs. 11,23,35 At this point, it should be noted that a small variation in synthesis conditions may result in a large difference in quantum efficiency, even with the same experimental conditions, but different batches. Nevertheless, we ruled out this possibility by repeating the measurements, using completely different batches provided by the same company.…”
Section: Resultsmentioning
confidence: 99%
“…8 In addition, recent works have demonstrated the ability of QDs to act as nano-thermometers based on the thermal sensitivity of their fluorescence bands. [9][10][11][12][13][14] Based on all these outstanding properties, QDs have been successfully used to mark specific receptors in cell membranes, to measure intracellular temperature, and to label living embryos at different stages. 9,[15][16][17] Most of the QD-based bio-images reported up to now were obtained by using either CdSe or CdTe QDs, since both are currently commercially available with a high degree of quality.…”
Section: Introductionmentioning
confidence: 99%
“…These multicomponent materials are known as nanocomposites. Walker et al first characterized the temperature response of the photo-luminescence (PL) of colloidal QDs immobilized inside a polylaurylmethacrylate (PLMA) matrix [10] proving the suitability of QDs as temperature references for PL-based sensing applications. Other authors have also reported the use of different host polymers such as polystyrene (PS) [11] or polymethylmethacrylate (PMMA) [12] to embed QDs, and even coupling the light with the aid of optical fibers [13].…”
Section: Introductionmentioning
confidence: 99%
“…This versatility leads to numerous photonic applications, such as optical fiber amplifiers, 1,2 color displays using light-emitting diode arrays, 3 optical temperature probes, 4 and biomedical imaging. 5 Conjugation of QDs with antibodies yields biomarkers that compete with traditional organic fluorescent tags in terms of biocompatibility, excitation and filtering simplicity, and photostability.…”
mentioning
confidence: 99%